SISTEM MONITORING SINYAL ELEKTROKARDIOGRAM (EKG) MENGGUNAKAN THINGSPEAK CLOUD COMPUTING - Amin Ajaib Maggang; Beby H. A. Manafe; Sarlince O. Manu; Johanis F. M. Bowakh (Universitas Nusa Cendana, 2021)
Developments in electronics and software have led to many cloud server applications that can be integrated with Arduino Uno to create an inexpensive cardiovascular health monitoring system. Therefore, this study aims to build a heart health monitoring system based on the internet of things by utilizing the free ThingSpeak server account and the AD8232 ECG sensor. The results show that the developed system can send ECG data and display it on the ThingSpeak server, although only the QRS and RR segments of the ECG signal can be displayed properly and meet its normal standards. Apart from this, the system is also able to automatically calculate and display the heart rate on the output of the ThingSpeak server every 15 seconds, so that heart health can be monitored in real-time.